Best Lessons for Well‐being From Psychologists: Implications for the Public and for Psychology. (December 2013) - Thompson, Anthony; Boxall, Dianne; Hodgins, Gene; Patrick, Kent
<x xml:space="preserve">Abstract</x> Psychological knowledge contributes in many ways to promoting individual and social functioning. Within the discipline, an energetic culture of public education has grown in recent decades with the objective of elucidating the relevance of psychology. There are many examples of translating and communicating psychological science for public consumption. In the current study, we interviewed 30 psychologists to explore their ideas about helping people to live well and be psychological healthy. Through qualitative analysis of transcript data, we identified three "best lessons" for well‐being. The lessons concerned (a) improving relationships, (b) understanding the way that thoughts influence adjustment, and (c) adopting an orientation to self and life that facilitates personal growth. We interpreted these as representing pragmatic wisdom in terms of their content and the process by which interviewees distilled their knowledge and experience. The best lessons can serve as a useful psychological triad for public dissemination. It would also be beneficial for psychologists in training to recognise pragmatic wisdom as a meta‐cognitive process and to develop skills for communicating psychological science to broad audiences.